Editors' Choice—Hydrogen Centers in β-Ga2O3: Infrared Spectroscopy and Density Functional Theory. (1st January 2019) - Qin, Ying; Stavola, Michael; Fowler, W. Beall; Weiser, Philip; Pearton, Stephen J.
Abstract : β-Ga2 O3 is a transparent conducting oxide with a wide bandgap (4.9 eV) whose properties are generating widespread interest. It has been found that hydrogen can play a key role in the conductivity of Ga2 O3 by passivating deep defects and acting as a shallow donor. Recent vibrational spectroscopy experiments have found a dominant hydrogen center with a polarized O-H line at 3437 cm −1 . These experiments along with theoretical analysis assign this line to a defect consisting of two equivalent H atoms trapped at a relaxed Ga vacancy. An expansion of this research has involved annealing treatments as well as measurements at different crystal orientations. These results have discovered a reservoir of "hidden" hydrogen in Ga2 O3 whose identification involves a variety of hydrogen centers associated with the Ga vacancy, as well as other possible species.